The prognostic value of soluble Klotho in patients with haemodialysis: a systematic review and meta-analysis - Qi-Feng Liu; Sha-Sha Li; Li-Xia Yu; Jian-Hua Feng; Li-Li Xue; Guo-Yuan Lu (SAGE Publishing, 2020)
Aim: The correlation between soluble Klotho (sKlotho) levels and clinical outcomes remains inconclusive for patients undergoing maintenance haemodialysis (MHD). We aimed to evaluate the potential predictive significance of sKlotho in this population by conducting a meta-analysis. Methods: PubMed, Embase, Web of Science and Cochrane Library were comprehensively searched for studies concerning the association between sKlotho level and clinical outcomes including cardiovascular (CV) events and all-cause mortality. The pooled hazard ratios (HR) and 95% confidence intervals (CI) were generated using either random or fixed effects models. Sensitivity and subgroup analyses were used to explore heterogeneity sources. Results: Eight prospective studies with 992 MHD participants were included and reduced sKlotho levels predicted more adverse outcomes in this meta-analysis. The pooled HRs and 95% CIs related to CV events, mortality, or composite outcomes were 1.73 (95% CI 1.08-2.76, p  = 0.02), 2.34 (95% CI 1.34-2.07, p  = 0.003) or 1.75 (95% CI 1.19-2.57, p  = 0.005). Moderate heterogeneity was observed in the composite adverse outcomes ( I 2  = 57%, p  = 0.05). Age and sKlotho level were the main sources of heterogeneities in the subgroup analysis. Conclusion: Lower sKlotho levels were associated with more CV events and all-cause mortality, suggesting that sKlotho may have predictive value in CKD patients receiving haemodialysis.